Debt maturity dispersion and the cost of bank loans - Chiu, Wan-Chien; King, Tao-Hsien Dolly; Wang, Chih-Wei (Journal of Corporate Finance, 2021)
This paper examines the relation between corporate debt maturity dispersion and the pricing and terms of bank loans. Analyzing a sample of U.S. bank loans from 2002 to 2016, we find that firms with a dispersed debt maturity structure pay a lower interest rate. The rate-reduction effect is significant only for firms without a credit rating. For these firms, spreading debt maturity dates also results in lower commitment fees, fewer covenant restrictions, and less collateral in their loan contracts. The impact of debt maturity dispersion on the pricing and structure of bank loans is stronger when borrowers have higher rollover risk or when the need for monitoring is greater. Our results suggest that dispersion in debt maturity structure mitigates the agency problem associated with shareholder–creditor conflicts by reducing rollover risk and alleviating the need for monitoring, which results in borrowers receiving more favorable terms in loan contracts.